Organizational Resilience in the Face of Disruptions - Adeyemi Folake (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
This research looks into the topic of corporate resilience, specifically how well-established businesses handle change and how they recover from setbacks. Data on organizational resilience strategies and practices are gathered through a mixed-methods approach that includes questionnaires and in-depth interviews with organizational leaders. The results stress the significance of having an adaptable culture, spending money on new technologies, using sound financial planning and management techniques, and being well-prepared. The study's findings shed light on tactics that businesses can employ to strengthen their ability to withstand and recover from disturbances. Organizations can better weather the inevitable upheavals of today's fast-paced business climate by adopting these practices and procedures.